2012
DOI: 10.1556/jep.10.2012.4.1
|View full text |Cite
|
Sign up to set email alerts
|

The myth of hidden ovulation: Shape and texture changes in the face during the menstrual cycle

Abstract: In recent years, evidence has been gathered indicating increased attractiveness of female faces at the point of ovulation. In this paper, we asked what changes in facial appearance occur during menstrual cycle that lead to this shift in attractiveness. We analysed facial photographs of 20 young women with a normal cycle. We found evidence for textural changes, as well as shape changes that might account for the ovulatory peak in attractiveness. Generally, facial shape at ovulation is perceived as more attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
4
45
2
Order By: Relevance
“…Such results can be interpreted as men's ability to detect 'leaky cues' to ovulation, serving men in the arms race between women's effort to conceal ovulation and men's selective advantage to detect it. Alternatively, men's preference for ovulatory cues might occur because facial signals of ovulation are identical to what is typically seen as attractive in women's faces [8,15]. In this case, women (like men) should find ovulatory faces more attractive than luteal faces, which was not the case in this study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Such results can be interpreted as men's ability to detect 'leaky cues' to ovulation, serving men in the arms race between women's effort to conceal ovulation and men's selective advantage to detect it. Alternatively, men's preference for ovulatory cues might occur because facial signals of ovulation are identical to what is typically seen as attractive in women's faces [8,15]. In this case, women (like men) should find ovulatory faces more attractive than luteal faces, which was not the case in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Women were shown pairs of faces, one of which depicted an ovulatory face, the other a luteal face, and were asked to choose the more attractive woman. According to some authors ( [8], see also [15]), facial signals of ovulation might be identical to what is typically seen as attractive in women's faces. If this were true we would expect that both women and men should find female faces showing ovulation cues more attractive.…”
Section: Introductionmentioning
confidence: 97%
“…Recent investigations have shown that near peak fertility, women's faces are not only rated as more attractive by observers, but are also characteristically more feminine in appearance (Oberzaucher et al, 2012;Puts et al, 2013;Roberts et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, no correlation was found between facial fluctuating asymmetry and the ratio of second to fourth digits, which relates to prenatal exposure to sex hormones [375,376]. By contrast, short-term effects of hormonal levels on asymmetry have been shown, as the asymmetry of facial shape changes during the menstrual cycle of individual women [294]. Finally, some human behavioral traits are also correlated with fluctuating asymmetry of facial shape, such as the tendency to cooperate or defect in the "prisoner's dilemma" game [374,375], some aggressive behaviors in adolescents [248], and personality traits [377,378].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 95%
“…Following this, asymmetry can be quantified as the difference between the original and reflected outline or surface. This method has been used with semilandmarks for 2D outlines [148,294,295] and with 3D surfaces [204,296]. A similar idea was the basis for an ad-hoc method to determine the asymmetry in a single outline contour using image analysis [297].…”
Section: Outline Methodsmentioning
confidence: 99%